Perioperative Complications of Robot-Assisted Laparoscopic Surgery Using Three Robotic Arms at a Single Institution - Yim, Ga Won (Yonsei Med J, 2015)
PURPOSE: The aim of this study was to evaluate perioperative complications of robot-assisted laparoscopic surgery in gynecology. MATERIALS AND METHODS: Patients who underwent elective robot-assisted laparoscopic surgery between February 2006 and December 2013 were identified. Robotic procedures were performed using the da Vinci robotic system. Patient demographic data and operative outcomes were prospectively collected in a computerized database and extracted for this study. RESULTS: Two hundred and ninety eight patients were identified during the study period. One case was converted to conventional laparoscopy due to mechanical failure of the robot system before the procedure and excluded from review. The median age and body mass index of patients were 48 years and 23.0 kg/m(2), respectively. The majority (n=130, 43.6%) of operative procedures was radical hysterectomy, followed by endometrial cancer staging (n=112, 37.6%), total hysterectomy (n=39, 13.1%), and myomectomy (n=17, 5.7%). The median operative time, estimated blood loss, and postoperative hospital stay were 208.5 min, 184.8 mL, and 8.9 days, respectively. The overall complication rate was 18.8% and that for only oncologic cases was 16.1%. Intraoperative complications (n=5, 1.7%) consisted of three vessel injuries, one bowel content leakage during an appendectomy during endometrial cancer staging and one case of bladder injury during radical hysterectomy. Early and late postoperative complications were 14.4% and 2.7%, respectively. Five patients (1.7%) experienced grade 3 complications according to Clavien-Dindo classification and therefore needed further intervention. CONCLUSION: Robot-assisted laparoscopic surgery is a feasible approach in gynecology with acceptable complications.